Multimodal and site-specific plasticity of amygdala parvalbumin interneurons after fear learning - Lucas, Elizabeth K. (Neuron, 2016)
Stimulus processing in fear conditioning is constrained by parvalbumin-interneurons (PV-INs) through inhibition of principal excitatory neurons. However, the contributions of PV-IN microcircuits to input gating and long-term plasticity in the fear system remain unknown. Here we interrogate synaptic connections between afferent pathways, PV-INs, and principal excitatory neurons in the basolateral amygdala. We find that this region is populated by at least two functionally distinct PV-IN networks based on nucleus location. PV-INs in the lateral (LA), but not the basal (BA), amygdala possess complex dendritic arborizations, receive potent excitatory drive, and mediate feedforward inhibition onto principal neurons. After fear conditioning, PV-INs exhibit nucleus- and target-selective plasticity, resulting in persistent reduction of their excitatory input and inhibitory output in LA but not BA. These data reveal previously overlooked specializations of PV-INs within amygdala subnuclei and indicate specific circuit mechanisms for inhibitory plasticity during the encoding of associative fear memories.